2002
DOI: 10.1021/je0200766
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressure and Dissolution Enthalpy Measurements in Ternary {H2O + NaCl + Na2SO4} System between 298 K and 363 K

Abstract: A nonisothermal static device was used to make measurements of vapor pressures in the ternary {NaCl (1) + Na2SO4 (2) + H2O (3)} system between 298 K and 363 K with molality ratios m 1/m 2 = 1/10 and m 1/m 2 = 1/1. Experimental data were fitted using empirical relation proposed by Appelblat. Dissolution enthalpies of both anhydrous sodium chloride and sodium sulfate in water were also measured up to saturation conditions at 297.8 K, 317.5 K, and 332.4 K (with m 1/m 2 = 1/10, m 1/m 2 = 1/1, and m 1/m 2 = 10/1, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Figure 4 shows the activity of H 2 O in NaCl + Na 2 SO 4 solutions. At different NaCl/Na 2 SO 4 concentration ratios, our model accurately predicts the H 2 O activities, and suggests that H 2 O activities of this mixed salt solution are not sensitive to the temperature, which is consistent with the experimental data (Marliacy et al 2003). Osmotic coefficients of aqueous NaCl + MgCl 2 solutions are predicted and shown in Figure 5.…”
Section: Aqueous Solution Propertiessupporting
confidence: 84%
“…Figure 4 shows the activity of H 2 O in NaCl + Na 2 SO 4 solutions. At different NaCl/Na 2 SO 4 concentration ratios, our model accurately predicts the H 2 O activities, and suggests that H 2 O activities of this mixed salt solution are not sensitive to the temperature, which is consistent with the experimental data (Marliacy et al 2003). Osmotic coefficients of aqueous NaCl + MgCl 2 solutions are predicted and shown in Figure 5.…”
Section: Aqueous Solution Propertiessupporting
confidence: 84%
“…18-20 show the model results for molal dissolution enthalpy for the ternary system at the NaCl to Na 2 SO 4 molality ratios of 0.1, 1 and 10, respectively. The model results show excellent matches between the calculated values and the exper- [12], ( ) m1/m2 = 0.1, Marliacy et al [12], (᭹) data of Na2SO4-H2O [31], ( ) data of NaCl-H2O [16]. imental data.…”
Section: The Nacl + Na 2 So 4 + H 2 O Ternary Systemmentioning
confidence: 58%
“…Applying the eNRTL model, Marliacy et al [11] obtained very good agreement between experimental and calculated values of dissolution enthalpies and osmotic coefficients for the Na 2 SO 4 + H 2 O binary. Marliacy et al [12] further examined and confirmed the abilities of both the eNRTL model and the Pitzer model to represent simultaneously the dissolution enthalpies and the activities of water for the NaCl + Na 2 SO 4 + H 2 O ternary.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations